Physiology and Growth Performance of Gallus gallus domesticus Supplemented with Algal Extracts - ZU Abideen; M Farooq; T Ruby; AA Khan (Brazilian Journal of Poultry Science)
ABSTRACT The present study aimed to determine how dietary Arthrospira platensis (Spirulina) and Chlorella vulgaris extract (CVE) supplementation affects growth performance, hematological parameters, serum biochemistry, and blood hormones in Gallus gallus domesticus. The experiment included 70 chickens grouped across seven treatment groups consisting of a control group along with Spirulina doses from 0.25g/L to 5g/L, and CVE doses from 0.25g/L to 5g/L. The seven-week trial aimed to monitor how dietary interventions affect physiology in Gallus domesticus. Study findings showed that the supplementation treatment showed substantial impacts on both body development and biological functioning. Group 3 (2.5g/L CVE) had the greatest body weight gain of 35.50 ± 0.58 g (p<0.001), and Group 1 (2.5g/L SP) had the lowest cholesterol measurement of 125.00 ± 0.58 mg/dL (p<0.001). Group 6 (5g/L SP + 5g/L CVE) achieved the highest platelet count at 161.00 ± 0.58 x 10³/µL (p<0.001) along with a moderate cholesterol increase to 155.00 ± 0.58 mg/dL (p<0.001). The blood triglyceride concentrations decreased similarly in Group 1 (127.00 ± 0.58 mg/dL) compared with Group 6 (122.00 ± 0.58 mg/dL). Group 3 (2.5g/L CVE) demonstrated elevated hemoglobin together with RBC counts, whereas Group 6 (5g/L SP + 5g/L CVE) showed optimal platelet counts. Thyroid hormone levels remained unaffected. The combined use of Spirulina and CVE at the same level of 2.5g/L effectively reduced cholesterol together with triglycerides and enhanced both hemoglobin production and RBC counts. The combined treatment using 5g/L SP with 5g/L CVE delivered the most comprehensive results by improving body weight, platelet count, and biochemical assessments. The combination of 5g/L SP and 5g/L CVE improved body weight, platelet count, and biochemical markers. Future research should determine the most effective dosages and long-term benefits regarding poultry productivity improvement.